2022
DOI: 10.1177/03057356221091313
|View full text |Cite
|
Sign up to set email alerts
|

Alpha oscillations related to self-other integration and distinction during live orchestral performance: A naturalistic case study

Abstract: Ensemble music performance requires musicians to achieve precise interpersonal coordination while maintaining autonomous control over their own actions. To do so, musicians dynamically shift between integrating other performers’ actions into their own action plans and maintaining a distinction between their own and others’ actions. Research in laboratory settings has shown that this dynamic process of self-other integration and distinction is indexed by sensorimotor alpha oscillations. The purpose of the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 88 publications
1
0
0
Order By: Relevance
“…Conversely, alpha oscillations were enhanced when the players were familiar with each other's parts but their performances were slightly desynchronized. This was associated with greater reliance on self-other segregation processes (Novembre et al, 2016; see also Christensen et al, 2022 for a similar result obtained measuring from a small orchestra). Shifting to multi-brain measures, a recent study reported higher INS in the gamma band when pianists were unfamiliar with each other's part (Gugnowska et al, 2022).…”
Section: Neural Processessupporting
confidence: 65%
“…Conversely, alpha oscillations were enhanced when the players were familiar with each other's parts but their performances were slightly desynchronized. This was associated with greater reliance on self-other segregation processes (Novembre et al, 2016; see also Christensen et al, 2022 for a similar result obtained measuring from a small orchestra). Shifting to multi-brain measures, a recent study reported higher INS in the gamma band when pianists were unfamiliar with each other's part (Gugnowska et al, 2022).…”
Section: Neural Processessupporting
confidence: 65%